Tendência secular de internações por causas sensíveis à atenção primária entre menores de um ano no estado de São Paulo, Brasil - Lobo, Ianna Karolina Veras [UNIFESP] (2018)
The purpose of this article is describe the causes and trends of primary health care sensitive hospitalizations (ICSAP) in children under one year of age between 2008 and 2014, state of São Paulo, Brazil. It is an ecological study with descriptive and analytical characteristics, based on secundary data from the national information system of health. Hospitalizations were classified according to Brazilian list of hospitalizations due to ICSAP, considering the age groups: Early Neonatal, Late Neonatal and PostNeonatal. A linear regression models were adjusted for trends analysis of hospitalizations. Were analyzed 851.713 hospitalizations in children under one year of age occurred, of which, 22,6% were ICSAP. The main groups with decreases were: Bacterial pneumonia (7,10%) and Nutritional disorders (7,70%) in Early neonatal. The main increases were: Disease related to prenatal/childbirth (+10,14%) and Immunosuppressive diseases and avoidable conditions in Postneonatal (+14,13%). Pertussis and congenital syphilis were the main causes of hospitalization. The results showed a deficiency in child health in primary care system in the state of Sao Paulo. The estimated trends should be used for planning of costeffective strategies to prevent and control causes of the hospitalizations in children under one year of age.